Autophagy functions as an antiviral mechanism against geminiviruses in plants - Haxim, Yakupjan; Ismayil, Asigul; Jia, Qi; Wang, Yan; Zheng, Xiyin; Chen, Tianyuan; Qian, Lichao; Liu, Na; Wang, Yunjing; Han, Shaojie; Cheng, Jiaxuan; Qi, Yijun; et al. (eLife, 2017)
Autophagy is an evolutionarily conserved process that recycles damaged or unwanted cellular components, and has been linked to plant immunity. However, how autophagy contributes to plant immunity is unknown. Here we reported that the plant autophagic machinery targets the virulence factor βC1 of Cotton leaf curl Multan virus (CLCuMuV) for degradation through its interaction with the key autophagy protein ATG8. A V32A mutation in βC1 abolished its interaction with NbATG8f, and virus carrying βC1V32A showed increased symptoms and viral DNA accumulation in plants. Furthermore, silencing of autophagy-related genes ATG5 and ATG7 reduced plant resistance to the DNA viruses CLCuMuV, Tomato yellow leaf curl virus, and Tomato yellow leaf curl China virus, whereas activating autophagy by silencing GAPC genes enhanced plant resistance to viral infection. Thus, autophagy represents a novel anti-pathogenic mechanism that plays an important role in antiviral immunity in plants.
Keywords: Autophagy; geminivirus; antiviral immunity; βC1; ATG8; plant-virus interaction